Implementation of Nursing Ethics at Nort Moyo Health Center - Handayani, Asri; Rafi’ah, Rafi’ah; Lestari, Ana; Sholihah, Nur Arifatus (Journal of Midwifery and Nursing, 2024)
The problem of ethical behavior in nursing services will have an impact on the emergence of a feeling of dissatisfaction with the nursing services provided. Patients will feel that their needs are not being met and feel that they are not getting attention from nurses. Ethical issues in nursing often cause conflict in relationships between patients and colleagues. Ethical behavior problems that occur in the nursing process are a sense of injustice in nursing services, a lack of attention and concern for patients, ignoring patient rights, a lack of respect for patients, and high demands for professional ethics in every nursing service. The aim of this research is to determine the implementation of nursing ethics for nurses at the North Moyo Health Center, as well as the obstacles to implementing nursing ethics at the North Moyo Health Center. This research is empirical juridical research. This research is a descriptive analysis. Field research was carried out through interviews with research subjects using open-ended interviews and deep questions. The study data were analyzed qualitatively and presented in descriptive form. Based on research results, the application of ethics in providing health services at the North Moyo Community Health Center is optimal in accordance with standard operating procedures, codes of ethics, and applicable laws and regulations